Towards Active Rotor Analysis using Viscous Vortex Particle Method - Kumar, S.; Rauleder, J.; Yavrucuk, I. (My University, 2023)
This study explores the potential of the incompressible viscous vortex particle method (VVPM) formulation to model the unsteady rotor wake effects on blade aerodynamic loads. Preliminary validation results have been presented verifying the VVPM formulation. The particle method is coupled with a comprehensive rotor aeromechanical analysis code Dymore in order to improve the rotor wake modelling capability of the overall rotor analysis setup. The coupled Dymore+VVPM framework was verified by using static as well as dynamic wing cases in order to assess the ability of VVPM to accurately model wake induced velocities. The current study is the first step towards active rotor analysis using this coupled framework. Consequently, the ability of VVPM to capture unsteady aerodynamic effects due to wing pitching as well as active morphing was tested.
Keywords: Aerodynamics